Akty informacyjne administracji i ich identyfikacja przez środki masowego komunikowania - Fischer, Bogdan (Kwartalnik Prawa Publicznego, 2016)
At present, the excess of information, the selection and distribution of which is done by the mass media, requires the assessment of the sources, the continuous identification and the characterization of the information. Information plays a key role both from the point of view of the state, referred to as the “information state” as well as from the point of view of human rights and “information society”. This article is intended to make a contribution to the mass media’s identification of information processes in the public administration. Its findings are intended to permit a shorter systematization of the acts that fall within the scope of these processes. The need for such systematization arises from the need to draw attention, in the context of mass communication, to the distinction of these particular administrative acts. Without administrative information, the rule of openness in the functioning of public authority cannot be realized under the conditions of the modern democratic rule.